PROGRAM SIBAR DALAM UPAYA MONITORING KESEHATAN MENTAL REMAJA SEKOLAH DI MASA PANDEMI - Versiandika Yudha Pratama; Melisa Melisa (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The Covid-19 pandemic has made teaching and learning activities in schools stopped and learning is carried out online or distance learning. The cessation of the teaching and learning process in schools affects the mental health of students which has an impact on stress due to the large number of tasks during online learning. There needs to be a forum that is able to direct these students to more positive activities, one of which is the Sinau Bareng Forum (SiBar). This SiBar activity was attended by 15 school teenagers from Bugangan Village. Some of the activities carried out at the SiBar Forum include socializing the introduction of mental health, Ruang Peka sessions, and consultations on stress problems. The SiBar forum that was held received a positive response where the level of participant satisfaction with the implementation of the SiBar was seen that 86.67% percent were very satisfied and as many as 13.33% said they were satisfied